2012
DOI: 10.1007/s12253-011-9486-4
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometry-Based Salivary Proteomics for the Discovery of Head and Neck Squamous Cell Carcinoma

Abstract: The 5-year survival rates for cases of head and neck squamous cell carcinoma (HNSCC) are only some 60%, mainly because 20%-40% of the patients develop a local relapse in the same or an adjacent anatomic region, even when the surgical margins are histologically tumour-free. Tumours are often discovered in an advanced stage because of the lack of specific symptoms and the diagnostic difficulties. The more advanced the stage of the tumour, the more invasive the diagnostic and treatment interventions needed. An ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…LC-MS/MS analysis is an effective research strategy for global biomarker discovery, as demonstrated in many cancer types including oral SCC (36), head and neck SCC (37)(38)(39) and melanomas (40)(41)(42). Using patient samples such as fresh biopsies, serums and cell lines, MS analysis has led to the identification of novel protein biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…LC-MS/MS analysis is an effective research strategy for global biomarker discovery, as demonstrated in many cancer types including oral SCC (36), head and neck SCC (37)(38)(39) and melanomas (40)(41)(42). Using patient samples such as fresh biopsies, serums and cell lines, MS analysis has led to the identification of novel protein biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…MALDI-TOF-MS analysis can precisely separate and identify target proteins or peptides according to their mass-dependent velocities (m/z) (Ketterlinus et al 2005). It has recently been wildly applied to the diagnosis of cancer, such as prostate cancer (Villanueva et al 2006), oral cancer (Cheng et al 2005), thyroid cancer (Villanueva et al 2006), hepatocellular carcinoma (Liu et al 2014), bladder cancer (Schwamborn et al 2009), breast cancer (Hamler et al 2004), head-andneck squamous cell carcinoma (Jarai et al 2012), glioblastoma (Kumar et al 2010) and colorectal cancer (Deng et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Oral epithelial cells, including cells of the buccal mucosa, tongue, small salivary glands as well as the parotid and submandibular salivary glands in humans (Dreier et al, 1998) also express AnxA1. This protein is also present in human mucosal secretions such as bronchoalveolar lavage fluid (Smith et al 1990) and more recently been detected in human saliva (Lorenz et al, 2011;Jarai et al, 2012).…”
Section: Introductionmentioning
confidence: 92%